Contemporary Andean Aesthetics” The Human Figure in Ayacuchana Painting 2000 – 2020 - Meza Untiveros, Miguel Angel (2024)
Ayacucho painting of the human figure genre has a significant development in compositional and stylistic aspects. The Felipe Guamán Poma de Ayala School of Fine Arts has played a very important role in this process of adaptation, learning and authenticity, having national and international art schools as academic models. In this way, a traditional and figurative painting is visualized, despite social, scientific and technological changes. The pictorial representation of the Andean man and woman is broad and dynamic, they are inserted within the compositions that express tradition and customs of a changing context; in this sense, the following question arises: What symbols does Ayacucho painting of the human figure genre use today? To answer this question, various works will be described and analyzed from an iconographic and iconological perspective, in this way determining the following hypothesis: Ayacucho painting of the human figure represents its traditions and customs in a symbolic way and is called "Contemporary Andean Aesthetics."